Analisis Akuntabilitas Keuangan Sakti Sebelum dan Saat Pandemi Covid-19 - Erna Puspita; Sigit Puji Winarko (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2021)
In early 2020, to be precise in March 2020, the Indonesian government officially announced Covid-19 as a national pandemic, since then many entities have experienced a decline in their financial performance due to decreased purchasing power due to inability to carry out activities properly and even many entities that have decreased their financial performance. had to close down his business. This study aims to analyze the financial accountability performance of KSP Sakti Kota Kediri in 2019 and 2020, and to analyze whether there are differences in the financial accountability performance of KSP Sakti Kota Kediri before and during the Covid-19 pandemic. Data analysis was carried out by calculating all indicators used as a tool to measure the performance of KSP Sakti, in accordance with the Decree of the Minister of Cooperatives and MSMEs No. 43 of 2004. Meanwhile, the hypothesis testing used a different test using the Paired Sample T-Test. From the results of different tests using the Paired Sample T-Test, the Sig. amounting to 0.440 which is greater than the significant level of 5%, this means that there is no difference between the financial accountability performance of KSP SAKTI before and during the pandemic. If you look at the financial accountability data for 2019 and 2020, of the sixteen indicators, as many as seven indicators have decreased, but the decline is very small.